Decorrelating compensation scheme for coefficient errors of a filter bank parallel A - Sanada, Y.
In this letter, a parallel analog-digital (A/D) conversion scheme with a filter bank for low intermediate-frequency receivers is presented. The analysis filters of the filter bank divide the frequency components of the received signal, and achieve parallel A/D conversion. Therefore, the required conversion rates and the resolution of the A/D converters can be reduced and the receiver can demodulate wideband signals. As the analysis filters consist of analog components, their coefficients include errors. These errors cause mutual interference between signals in orthogonal frequencies. In order to remove this interference, a decorrelating compensation scheme is proposed.
Keywords: Coefficient errors; Decorrelating compensation scheme; Filter bank; Interference cancellation; Intermediate-frequency receivers; Parallel A/D converter; Parallel analog-digital conversion scheme; Software radio